An Appraisal of Plants Used as Health Foods in Mozambique - Assane, R. S. S.; Cuinica, L. G.; Bell, V.; Chabite, I. T.; Fernandes, T. H. (European Journal of Applied Sciences, 2023)
A third of Mozambique is considered conservational area and is extremely rich in animal, plant, and marine biodiversity ecosystems. Over 90% of the 33 million population still depends on traditional medicine to meet its primary healthcare needs. While diagnosis has been based on symptoms for lack of laboratories and healthcare staff, respiratory diseases have been rising and with the pandemics the prevalence and assistance to these disorders has increased. Readily available natural plants have been used for many decades as valuable agents due to their content in unknown and also well described phytochemicals. This short but concise research project aimed at supplying an overview of the currently known efficacy of some plant species used traditionally in the north of Mozambique specifically for respiratory diseases. Several secondary metabolites were investigated in some commonly used medicinal plants. This primary work on phytochemical profiling will be useful for future pharmacological, molecular, toxicological, and pre-clinical assessments, contributing to public health pursuits and for guiding future investigations. An oral questionnaire in local language, included questions about the popular name of the plant, therapeutic indication, part used, form of preparation, route of administration, dosage/ingredients, duration of treatment, and adverse effects. Pre-treatment, extract collection, and qualitative phytochemical analysis were investigated on 5 main selected plant species. The most cited species used were Ficus religiosa L, Olax dissitiflora Oliv, Eucalyptus globulus Phil., Catunaregam spinosa (Thunb.) Tirveng, and Eulychnia acida Phil. which revealed several secondary metabolite classes such as alkaloids, flavonoids, tannins, and saponins, with a general absence of coumarins. Plant remedies were prepared mainly as infusion, decoction and maceration, and the ways of administration were oral, inhalation and bath. The most commonly used parts in the treatment were the roots and leaves, with the bark and stem least used.